Arrows of Desire: Dance and Power in Transnational Cinema - May Telmissany (Revue des Mondes Musulmans et de la Méditerranée)
This article focuses on the complexity of oriental belly dancing as it has become in recent years an expression of female joy and “will to power” celebrated by Arab and North African diaspora filmmakers. Associated with female emancipation rather than moral decline, the practice of oriental dancing is perceived as a symbol of subaltern expression, a site of female solidarity and a tool for sexual liberation. The rehabilitation of this practice in transnational cinema opens up a new space to reflect upon the "dispositifs" of desire and power as the immanent principle of the reorganization of forces in society. Using Deleuze and Guattari's conceptualization of desiring machines, this article is an attempt to disentangle the problematic relationship between dance, desire and power in four films directed by North African filmmakers living in France: Satin Rouge [Raja Amari, Tunisia, 2002], Viva Laldjérie and Délice Paloma [Nadir Moknèche, Algeria, 2004 and 2007], and Whatever Lola Wants [Nabil Ayouch, Morocco, 2007].